The templates of lesson plans: analysis and application of technology - Kubilinskienė, Svetlana; Dagienė, Valentina (Lietuvos matematikos rinkinys, 2010)
Lesson plan – an important methodological component of the learning process. Purpose of the article – analyze the current situation and suggest how information technology can assist the development of lesson plans, their accumulation and retrieval, thus ensuring their for effective application. The authors’ disclosures problems of lesson plans creation and its description and did comparative analysis of information and lesson plans templates which provided LO storages. The authors identified the main components of lesson plans and its description, which based are proposed the technology–based lesson plans templates and its description creation. This development of lesson plans and descriptions for educators will allowed re–use didactic resources (lesson plans) as an effective learning tool.
Keywords: technology enhanced learning; lesson plans template; learning object; metadata